Neuronal Sik1 in the Hypothalamic Paraventricular Nucleus Decreases Blood pressure Elevation Following a High-Salt Diet - Wei Zhang; Ping Wang; Shuya Qi; Na Huang; Qingyun Huang; Zhongxin Guo; Weifeng Wu; Guohe Tan (Molecular Neurobiology, 2026)
Blood pressure (BP) regulation involves complex interactions between peripheral organs and the brain. As a key area gating BP regulation, how the hypothalamic paraventricular nucleus (PVN) modulates salt‑sensitive hypertension remains unclear. Here, we found that Sik1, a member of the AMP-activated protein kinase family, was upregulated in PVN neurons of mice following a high-salt diet (HSD). When Sik1 was ablated, Sik1 knockout mice exhibited an increase in BP upon HSD feeding. Furthermore, specific deletion of the Sik1 gene in the nervous system by Nestin-Cre ( Nestin-Cre;Sik1 –/– ) resulted in elevated BP after high salt intake. Notably, AAV-Cre-mediated selective ablation of Sik1 in the PVN neurons was sufficient to cause BP elevation following an HSD. In combination with western blot and immunofluorescence detection, single-nucleus RNA sequencing combined with KEGG pathway analysis showed that Sik1 is predominantly expressed in arginine vasopressin (AVP)-positive neurons of the PVN, and in the absence of Sik1, the cellular NF-κB pathway in these neurons is downregulated by HSD. In addition, Sik1 deficiency led to microglial activation within the PVN under HSD conditions. These results suggest that Sik1 in AVP-positive neurons of PVN attenuates HSD-induced blood pressure elevation, possibly via modulation by the NF-κB signaling pathway. Our findings uncover a previously unrecognized role of neuronal Sik1 in salt‑sensitive hypertension pathophysiology, advancing our understanding of neurogenic blood pressure regulation.